2021
DOI: 10.1088/2053-1591/ac2f0b
|View full text |Cite
|
Sign up to set email alerts
|

New TiTaNbZrMo high-entropy alloys for metallic biomaterials

Abstract: The advantages of high entropy alloy with good comprehensive properties provide a potential opportunity to explore and develop new alloys suitable for human implantation. In this experiment, TiTaNbZrMo high entropy alloy was designed and prepared by alloy design and first principle. The calculation results predict that the phase composition of each high entropy alloy is BCC structure, and the designed high entropy alloy has structural stability; the non-equal atomic ratio TiNbTaZrMo high-entropy alloy has high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…From the content of 0.8 for these elements, the double formation of BCC was obtained for bioHEA (MoTa) x NbTiZr [41], with hardness values of 480-510 HV (x = 0.8 and 1). Analyzing the Ti 30 (NbTaZr) 60 Mo 10 [47], we observed that the hardness is 487 HV, close to the values found by Akmal et al [41], although the proportion of each element is different.…”
Section: Bioheas With Dual Phase Bccsupporting
confidence: 87%
See 2 more Smart Citations
“…From the content of 0.8 for these elements, the double formation of BCC was obtained for bioHEA (MoTa) x NbTiZr [41], with hardness values of 480-510 HV (x = 0.8 and 1). Analyzing the Ti 30 (NbTaZr) 60 Mo 10 [47], we observed that the hardness is 487 HV, close to the values found by Akmal et al [41], although the proportion of each element is different.…”
Section: Bioheas With Dual Phase Bccsupporting
confidence: 87%
“…Another four MoNbTaTiZr equimolar HEAs were studied in different works, three of them manufactured by arc melting [13,20,50] and one by induction [47]. For the works by Hua et al [20] and Wang and Xu [50], a hardness of approximately 500 HV was obtained, while for the work of Shittu et al [13] and Li et al [47], higher values were found: 657 and 619 HV, respectively.…”
Section: Bioheas With Dual Phase Bccmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2004, Yeh et al [7,8] proposed a method for creating alloys consisting of five to six metallic elements added in equal ratios. Many studies [9][10][11][12][13][14] have shown that the properties of such alloys, referred to as high-entropy alloys (HEAs), are superior to those of conventional alloys since the different atoms are randomly distributed in the atomic layer, which results in a disorderly (i.e., high-entropy) effect and limits the formation of brittle compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Among the traditional alloys, only depleted uranium alloys exhibit self-sharpening properties [4], but they have the problem of environmental contamination [5]. Fortunately, a emerging design paradigm of alloys with multiple-principal-element, often termed as high-entropy alloys (HEAs), has presented promising pathways for seeking new and improved alloys within a previously unexplored compositional/phase space [6][7][8][9][10][11][12][13][14][15][16]. Based on the average valence electron concentration strategy, a novel equimolar WMoFeNi high-entropy alloy with excellent self-sharpening properties has been successfully developed in our previous work [3].…”
Section: Introductionmentioning
confidence: 99%